Muscular Dystrophies - S, Sathasivam (IIUM Medical Journal Malaysia, 2012)
Huge strides have been made in the last two decades in our understanding of muscular dystrophies. This has led to better classification of this group of heterogeneous neuromuscular disorders based on clinical features, investigation results, and molecular and genetic pathophysiology. This review aims to discuss the major forms of muscular dystrophies, the useful investigations to diagnose them and the management strategies available at present.